I popoli indigeni e i loro diritti in America Latina. Dinamiche continentali, scenari nazionali - Cammarata, Roberto; Rosti, Marzia (Milano University Press, 2023)
In Latin America, and beyond, the indigenous question has raised a general call for radical democratization and decolonization, for greater justice and equity. This interdisciplinary collection of essays offers an updated overview of the situation and evolution of the rights of the indigenous peoples in that region, highlighting both the achievements and progress concerning individual national contexts, as well as the criticalities, contradictions and violations that has been characterizing the whole continent still today. These essays clearly show how the struggles of latin american indigenous peoples for the recognition and protection of specific cultural rights, new forms of autonomy and profound institutional transformations are contributing to redefine the language, theory and practice of human rights and modern State.